Quality Control Program for Radiotherapy MRI - Ranta, Iiro (fi=Turun yliopisto|en=University of Turku|, 2017)
Recent developments in magnetic resonance imaging (MRI) technology and imaging technique has enabled the use of MR images as the basis for radiation therapy planning (RTP) instead of widely used computed tomography (CT). Its superior soft-tissue contrast when compared to CT and reduction of radiation dose delivered to patients during the RTP process may lead to improved treatment results. Technological development has led to the emergence of MR-simulator scanners that include additional technology required for MRI-based RTP. Special techniques used in MR simulation place special requirements for the scanner performance. In order to verify proper scanner functionality, a regular quality control (QC) program has to be established to ensure the adequate performance. A QC program based on scanner manufacturer's QC tests and widely recognized QC programs of the American College of Radiology and American Association of Physicists in Medicine was designed for Philips Ingenia 1.5 T HP MR-simulator located at the radiotherapy department of Turku University Hospital. The QC program was evaluated by performing the QC tests regularly and analysing the results for the verification of stable scanner performance and adequate image quality needed in MR simulation. The purpose of the QC program was to improve the applicability of MRI for RTP when compared to CT. The QC program was successful and it can be used for future QC of the MR-simulator at Turku University Hospital.